Method for producing multi-layer composite film, multi-layer composite film and use thereof

Through coextrusion and biaxial orientation technology, using EVOH as the outer layer material and combining heat treatment and mitigation processes, the complexity and high cost of multilayer film materials are solved, and low shrinkage and high performance packaging materials are achieved.

JP2025016447AInactive Publication Date: 2025-02-04KUHNE ANLAGENBAU
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024167725
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-04-30
Filing Date
2024-09-26
Publication Date
2025-02-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing multilayer film materials have complex production processes, high resource consumption and high cost, making it difficult to achieve low shrinkage and high performance packaging materials.

Method used

Using a non-laminated multilayer composite film manufacturing method, ethylene-vinyl alcohol copolymer (EVOH) is used as the outer layer material through coextrusion and biaxial orientation techniques, and combined with appropriate heat treatment and mitigation processes, the interlayer structure is optimized to reduce shrinkage.

Benefits of technology

A multilayer film material with low shrinkage (≤5%) and high performance is achieved, improving processability and recyclability while maintaining excellent gas barrier, thermal stability and printing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016447000018
    Figure 2025016447000018
  • Figure 2025016447000019
    Figure 2025016447000019
  • Figure 2025016447000020
    Figure 2025016447000020
Patent Text Reader

Abstract

To provide a method for producing a coextruded and / or laminated, biaxially oriented composite film that can be used as a packaging material, particularly the packaging material for food products, and a resulting multilayer film that has improved processability and / or recyclability.SOLUTION: In a coextruded and biaxially oriented composite film with outermost layer consisting of or including EVOH, novel combinations of density of various layer components of the composite film and specific producing parameter such as stretch factor, relaxation factor, relaxation temperature and residual stretch factor are provided.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to coextruded and biaxially oriented multilayer films which can be used, for example, as packaging materials, in particular as packaging materials for food products, to their production methods and their use, preferably for packaging food products, luxury items or liquid or solid, in particular powdery, articles. However, the present application also relates to laminated multilayer films and corresponding production methods. [Background technology]

[0002] [Definition of the state of the art and the issues] On the other hand, laminated multilayer films are known from the state of the art to be excellent packaging materials. Thus, laminates consisting of at least two or three or even more independently produced layers are widely used in the packaging market. Essentially, a distinction is made between so-called "double" laminate films and so-called "triple" laminate films. "Double" laminate films are cast or blown extruded films that contain 5, 7 or 9 barrier film layers, which are laminated (bonded or glued) in a separate process with a biaxially oriented film of either polyethylene terephthalate (PET), polyamide (PA) or polypropylene (PP), again produced separately. Up to now, these films have only been produced and laminated successively in separate processes in order to achieve the sum of the desired and / or required properties. For example, two of the required properties (sealability and oxygen or aroma barrier properties) are realized in the extruded monolayer or multilayer film part, while the other properties, such as printability, heat resistance and mechanical strength, are realized in a separate biaxially oriented film part. Furthermore, it is common practice to specifically achieve or increase oxygen barrier properties by metallization, which is applied in a further process step.

[0003] [Table 1]

[0004] [Table 2]

[0005] Similarly, "tri-laminate" films are made in such a way that three films are manufactured separately and then later laminated (glued, adhered) together to produce the sum of the desired and / or required properties.

[0006] In this case, a biaxially oriented film made from PET, PA or PP is laminated with a separate aluminum foil, and then a cast film or blown film is extruded and laminated to this composite.

[0007] Here, extrusion cast or blown films are responsible for optimizing sealability, aluminum foil for barrier properties, and biaxially oriented films for printability, heat resistance, and mechanical strength. However, the disadvantage of laminated films is that their production is inherently complex, resource-intensive, and expensive, since multiple films must first be produced separately and then glued or adhered by hot melt or liquid adhesives in several successive process steps to finally obtain a laminated multilayer film, and the entire film composite is often very thick.

[0008] [Table 3]

[0009] [Table 4] [Brief description of the drawings]

[0010] Known double and triple film structures are shown in FIGS.

[0011] On the other hand, it is known from the state of the art that multilayer films are produced by coextrusion and biaxial stretching. The manufacturing process used for this purpose allows the multilayer film to be produced in just one step by coextrusion, where the subsequent bonding / lamination of the individual film layers with their associated disadvantages is completely eliminated. At best, biaxial stretching of the coextruded raw multilayer film is only performed to achieve the sum of the desired properties (sealability, heat resistance, barrier properties, mechanical strength, printability). Most of the required properties such as mechanical strength, heat resistance, printability, barrier properties (originally oxygen and gas barrier properties) other than sealability are achieved by using raw materials such as PET, PA, ethylene-vinyl alcohol copolymer (EVOH), polyvinyl alcohol (PVOH) and polylactic acid (PLA).

[0012] Thus, while materials such as EVOH, PVOH, PVDC and PA are preferably used to obtain oxygen or gas barrier, materials such as PET or PLA also offer significantly better barrier protection compared to polyolefin-based raw materials such as PE or PP, especially after orientation, ideally even after biaxial orientation.

[0013] In addition, by using PET or PA as the outermost layer of the film, excellent heat resistance and printability are achieved, especially after biaxial stretching.

[0014] PA and PET again contribute greatly to maintaining desirable mechanical strength, especially after biaxial orientation, in addition to good heat resistance, printability, and good barrier properties against gas and oxygen.

[0015] Thus, numerous composite materials in this regard are known from the prior art, such as, for example, DE 10 227 580 A1, DE 10 254 172 A1, DE 10 2006 046 483 A1, DE 10 2006 036 844 A1, EP 0 476 836 B2, EP 1 190 847 B1, EP 1 084 035 B1 and EP 1 985 444 A1.

[0016] However, the embodiments and methods known from the state of the art have one thing in common, namely that all these coextruded multilayer barrier films generally contain a relatively large shrinkage in the machine direction (MD) and in the transverse direction (TD), respectively, usually more than 20%, and in any case always more than 5%, which is advantageous or even desired for many applications such as shrink bags / lidding films or cover films.

[0017] [Table 5]

[0018] [Table 6]

[0019] However, multilayer barrier films produced by coextrusion or lamination and biaxial orientation have a configuration that shows relatively little or no shrinkage (5% or less, preferably 3% or less) in both the machine direction (MD) and the transverse direction (TD), and have sufficient barrier properties, sealability, heat resistance, mechanical strength and printability.

[0020] Additionally, processability and / or recyclability or remanufacturability of many conventional composite films leave much to be desired.

[0021] [Objective of the Invention] It is therefore an object of the present invention to provide a method for producing a coextruded and / or laminated and biaxially oriented composite film, preferably a coextruded and / or laminated and biaxially oriented multilayer barrier film, with improved processability and / or improved recyclability, and the resulting multilayer film, preferably a multilayer barrier film. Preferably, the composite film according to the present invention has at least one, preferably all of the following properties: sufficient oxygen and / or water vapor barrier properties, sealability, heat resistance, printability and mechanical strength, even without a further lamination step. It is particularly preferred if the composite film according to the present invention further has a relatively low or no shrinkage (5% or less, preferably 3% or less) in each of the machine direction (MD) and transverse direction (TD). Summary of the Invention

[0022] [Disclosure of the Invention] This object is solved by what is defined in the following subject matter and claims. According to the invention, a coextruded and / or laminated and biaxially oriented composite film is proposed, the outermost layer (a) of which consists of or comprises EVOH. Furthermore, a corresponding manufacturing method and use of the composite film are proposed. With regard to the coextruded and biaxially oriented composite film according to the invention, it is preferably provided that it is not laminated. Thus, in the manufacturing method of the multilayer composite film according to the invention, the method may not comprise a lamination step.

[0023] According to the present invention, a method for producing a multi-layer composite film is proposed, the method comprising at least the following steps: co-extruding and / or laminating at least three layers (a), (b) and (c); Layer (a) forms the outer surface of a composite film or forms the outer composite surface; Layer (c) forms the surface of the composite film that faces or contacts the article to be packaged; and Layer (b) is disposed between layer (a) and layer (c); wherein layer (b) consists of one or more layers (b1, b2, b3, b4, ...), preferably 2, 3 or 4 layers; stretching the coextruded or laminated composite film; and allowing the oriented or stretched composite film to relax; wherein the stretching is biaxial; a machine direction or longitudinal direction (MD) stretch factor of at least 2.0; the stretch factor in the transverse direction (TD) is at least 2.0; the sum of the machine direction (MD) stretch factor and the transverse direction (TD) stretch factor is at least 5.0; The composite film has a temperature of 70-130°C during stretching; Machine direction (MD) relaxation factor >0.00; Transverse direction (TD) relaxation coefficient exceeds 0.00; the sum of the relaxation coefficient in the machine direction (MD) and the relaxation coefficient in the transverse direction (TD) is at least 0.05 (=5%), preferably at least 0.1 (=10%), preferably at least 0.2 (=20%), in particular at least 0.4 (=40%); The composite film has a temperature during relaxation of 60 to 180°C, preferably 60 to 150°C, more preferably 60 to 120°C, and particularly preferably 80 to 100°C; the residence time during relaxation, preferably during relaxation at temperature, is preferably at least 2 seconds, more preferably more than 5 seconds, or the duration of relaxation is preferably at least 2 seconds, in particular more than 5 seconds; or the relaxation time is preferably at least 2 seconds, in particular 5 seconds or more, or the relaxation time is preferably at most 30 seconds, preferably at most 20 seconds, in particular at most 10 seconds; The residual stretch factor in the machine direction (MD) is at most 5.0; The residual stretch factor in the transverse direction (TD) is up to 5.0; Layer (a) has a density of at least 1.12 g / cm 3comprising or consisting of an ethylene-vinyl alcohol copolymer (EVOH) having a density of The layer (b) or layers (b1, b2, ...) each have a density of 1.00 g / cm 3 comprising or consisting of a thermoplastic resin having a greater density; and Layer (c) is 0.95 g / cm 3 The thermoplastic resin may comprise or consist of a thermoplastic resin having a density less than 1000 .mu.m.

[0024] Up to now, composite films in which EVOH is used as a layer component of the outermost layer (a) or in which layer (a) consists of EVOH are not known in the state of the art. It is known in the art to use EVOH as a material with good oxygen barrier properties. However, use for this purpose requires an inner position / arrangement of EVOH, since EVOH quickly loses its good oxygen barrier properties due to moisture permeation. Therefore, up to now, EVOH has been used as a layer structure or layer material simply sandwiched on both sides with protective layers such as polyolefins or polyamides that contain high water vapor barrier properties. However, the use of EVOH in general composite films for different purposes and in different ways or in different arrangements, for example as an outermost layer or a sealant layer (innermost layer; surface facing the packaged article), is not known up to now.

[0025] In contrast, according to the present invention, EVOH is purposefully used in layer (a), i.e. the outermost layer, which represents the outer surface of the composite. In this case, the outermost layer (a) comprises or consists of EVOH. However, it is not the properties of EVOH as an oxygen barrier that play a role when providing EVOH in the outermost layer (a). Rather, it has been surprisingly found that the use of EVOH in the outermost layer significantly improves the recyclability of the film compared to conventional composite films that comprise an outermost layer that comprises, for example, PA or PET. This is because EVOH comprises a melting temperature compared to the PA and PET materials that are conventionally provided in the outermost layer, such that the difference in melting temperature between the outermost layer and the sealant layer (innermost layer) is smaller. This allows the overall melting temperature required for recycling to be reduced, improving the recyclability of the composite film.

[0026] The inventors have also found that the outermost EVOH layer can further improve the mechanical properties of the film, such as stiffness and printability, compared to polyolefins such as PE or PP. For example, the higher melting temperature of EVOH, especially compared to these polyolefins, leads to an overall improvement in the processability of the composite film.

[0027] In the composite film according to the invention, the EVOH used in layer (a) has a viscosity of 1.12 g / cm 3 or more, preferably 1.13 g / cm 3 Above 1.13 to 1.22 g / cm 3 The EVOH used according to the present invention has an ethylene monomer content of 48 mol% or less, preferably 24-44 mol%. Thereby, the melting point of the EVOH is 160°C or more, preferably 180°C or more, more preferably 190°C or more. According to the present invention, the EVOH has a higher melting temperature than the resin of layer (c).

[0028] From the state of the art and in practical use, it has been found that materials such as PET and PA in the outermost layer are suitable for achieving the best possible printability and the highest possible heat resistance.However, materials such as PLA or EVOH are much more suitable in terms of printability, heat resistance and also processability than polyolefin-based raw materials such as PE or PP.

[0029] [Table 7]

[0030] [Table 8]

[0031] [Table 9]

[0032] In order to obtain sufficient barrier properties against oxygen and gases, raw materials such as PET, PA, EVOH, PVOH, and PVDC have been established.

[0033] [Table 10]

[0034] However, as is well known among experts, the barrier properties of many of these ingredients are only sufficient if they are adequately protected against moisture.

[0035] Therefore, when these materials provide barrier properties, they are always used in one of the middle or innermost layers of a film.

[0036] In order to obtain the best sealability, polyolefin-based raw materials such as PE or PP should in any case be used which contain the lowest possible sealing or melting temperature, as is known from practical experience.

[0037] [Table 11]

[0038] It is surprising that a raw material that is ideally used to achieve properties such as heat resistance, printability and oxygen barrier can be biaxially oriented and still have strength that polyolefins simply cannot match, especially after biaxial orientation.

[0039] In the optimal layer structure, an oxygen barrier layer would result from EVOH, PVOH or PA and would be placed in one of the middle or intermediate layers, and a sealant layer made of a heat-sealable polyolefin would be placed in the innermost layer.

[0040] Therefore, the outermost layer may also include portions of heat resistant and printable materials such as PET or PA.

[0041] Looking closely at the materials that offer specific advantages such as heat resistance, printability, oxygen barrier properties and strength, for example, all materials have a 1.0 g / cm 3 It has been found that the materials share the common features of having densities greater than 100° C., all of the materials are polar, and nearly all of the materials have melting temperatures greater than 160° C., especially greater than 170° C. or higher.

[0042] Further considering the materials preferably used for the sealant layer, all of them have a density of 0.95 g / cm 3 It has also been found that the melting point is less than 120°C and the density is less than 100°C.

[0043] [Table 12]

[0044] These 1.0g / cm 3Not all of these materials, with densities above 100%, are equally ideal for printability like PA or PET, or heat resistance like PET or PA, nor do they all contain the same high oxygen barrier properties like EVOH, PVOH or PA, nor do they all offer the same strength enhancements like PA or PET, but all of them, when combined in composite films, offer significantly improved properties over any polyolefin-based material, especially after biaxial orientation.

[0045] 1.0g / cm 3 Due to the different optimum properties of the raw material, with heat resistance, printability and oxygen barrier properties, having a density exceeding 100%, and the resulting ideal or preferred division into at least two separate layers, this division leads to a further very positive effect, namely a partially significant increase in the strength and stiffness of the film.

[0046] This effect is 1.0 g / cm 3 This is especially true if two layers containing ingredients with densities greater than 0.1 are spaced apart from each other in the overall composite of layers.

[0047] So, on the one hand, if the density is 1.0 g / cm 3 It is possible to select a layer structure in which the composite film comprises at least two separate layers, one of which forms the outermost layer and the other of which forms an intermediate layer, and the composite film forms the innermost layer and has a density of 0.95 g / cm 3 The heat sealable layer comprises a material, preferably a polyolefin, having a density less than 100° C. and a melting temperature less than 120° C.

[0048] Such a layer structure makes it possible to achieve many desirable properties (particularly sufficient oxygen and / or water vapor barrier properties, sealability, heat resistance, printability, and mechanical strength) in an excellent form, especially after biaxial stretching. However, the setting of desirable low shrinkage properties, especially after biaxial stretching, has not yet been solved.

[0049] This problem cannot be solved by the raw materials alone, at least when the produced film is biaxially stretched, so a suitable production method and / or suitable treatment is required to overcome this problem.

[0050] Particularly after stretching, and especially after biaxial stretching, polymers or films made from polymers may contain significant shrinkage, which may vary from polymer to polymer and may depend substantially on whether and how much heat or temperature is applied to the film.

[0051] That is, the higher the temperature and the longer the exposure time, the more the film will shrink.

[0052] Methods or treatments are known in the art that are used on uniaxially aligned films, and in particular on biaxially aligned films, to reduce shrinkage from the alignment film.

[0053] In particular for uniaxially and also biaxially oriented films, a post-treatment is known in which, after the stretching step, the film is placed over a tempering roll with as high a wrap as possible (so-called tempering roll), whereby heat or temperature is introduced into the film, i.e. it is thermally fixed, so that the residual shrinkage is reduced.

[0054] For the stretching of flat films, the so-called tenter frame process, in which the film is passed horizontally after stretching through a downstream oven and treated with hot air to reduce shrinkage, is also known as a post-treatment (tempering) or heat setting (thermal setting).

[0055] In the process according to the invention, the following stretching conditions are preferably used in combination: Stretching temperature in the range of -70 to 130 °C; - stretch factor in the machine or longitudinal direction (MD): at least 2; - stretch coefficient in transverse direction (TD): at least 2.0; and The sum of the stretch factor in the machine direction (MD) and the stretch factor in the transverse direction (TD): at least 5.0.

[0056] Furthermore, thermal post-treatment after stretching is also known from the so-called triple-bubble or multi-bubble process of tubular films. In this process, the film passes through an oven in tubular form and is often temperature-treated with hot air, similar to the tenter frame process. Alternatively, the film is treated with infrared radiation or hot steam in the triple-bubble process to reduce shrinkage due to stretching.

[0057] Various techniques are known for reducing shrinkage after biaxial orientation by applying temperature, but here, in addition to the level of applied temperature, the time or duration of the temperature shock is also an important factor.

[0058] However, heat / temperature treatment alone to reduce or even completely eliminate film shrinkage is only effective for some types of films and is not fully effective.

[0059] For example, films produced by the tenter frame process, such as BoPET, BoPA or BoPP (Bo=biaxially oriented), are stabilized by a very high heat treatment (heat setting) so that they contain almost no shrinkage.

[0060] The situation is similar for films that are biaxially oriented using the double bubble method and then heat set using tempering rolls or horizontal hot air ovens. Again, BoPP and BoPA films in particular may be treated or set by temperature alone, resulting in little or no shrinkage.

[0061] This is mainly due to the fact that these film types are pure in terms of polymer type, independent of the stretching process, and use only one type of raw material: BoPET (only PET), BoPA (only PA), and BoPP (only PP).

[0062] In this case, a high heat setting temperature, a temperature just below the softening point or melting point corresponding to the raw material can be selected for stabilization, so that shrinkage can be significantly reduced or eliminated by temperature treatment alone.

[0063] However, up until now this has been thought to be impossible for film types made from various raw materials, i.e. different types of raw materials, especially raw materials with very different softening and melting temperatures.

[0064] In fact, for example, there are no known coextruded or biaxially oriented films that contain a combination of different raw materials with widely differing softening and melting temperatures and that additionally exhibit little or no shrinkage upon stretching.

[0065] An exception are free-standing multilayer films produced by the tenter frame or double bubble process, which essentially contain the following layer structure (from inside to outside, HV=adhesion promoter): PP-HV-EVOH-HV-PP

[0066] Since homo-PP (homopolymer PP, melting temperature: 155-165°C) is used almost exclusively in combination with EVOH and EVOH grades with high ethylene content that have a lower melting temperature than those with low ethylene content (melting temperature: 170-180°C), these composites can in fact be stabilized at similar temperatures almost by heat treatment alone, reducing or eliminating shrinkage.

[0067] However, these PP-based multilayer films, which consist mostly of PP, do not exhibit the desired heat resistance and do not reliably exhibit the required printability.

[0068] PP is not an ideal raw material to use for the outermost layer, as even the most heat-resistant homo-PP grades melt below 170°C, PP is one of the most non-polar raw materials, and without further post-treatment is completely unsuitable for printing.

[0069] Also, as is well known in the market, these PP-based multilayer films have very low or only moderate sealability, i.e. relatively high sealing temperatures, due to the type of PP used and its fundamentally low sealing properties compared to preferred raw materials such as PE. Therefore, these films are conventionally post-laminated with PE-based films.

[0070] Thus, a multi-layer, coextruded and then biaxially oriented film that includes a sealant layer having a low melt temperature, and that includes an oxygen barrier layer that is not subsequently laminated, and that includes a heat resistant, printable (polar) outermost layer as well as an intermediate layer, and that includes no or minimal shrinkage, is not currently believed to be manufacturable.

[0071] This is because such multi-layer composites cannot be produced reliably or at all at the temperatures required to eliminate or reduce shrinkage to less than 5%, and more preferably to 3% or less, without further process ingenuity.

[0072] Even before the temperatures necessary to eliminate shrinkage are reached, the individual layers of the multi-layer composite will soften or melt, inevitably disrupting or at least severely impeding the film manufacturing process.

[0073] When or at what temperature the process failure or even interruption occurs is determined by the fact that the layer fraction of the entire film composite is >1.00 g / cm 3 0°C and having a melting temperature above 160°C, preferably above 170°C, i.e., a heat resistant material.

[0074] >1.00g / cm 3 If the mass fraction of the material having a density of 40% or more, based on the total mass of the layer structure of the film, and even more if the mass fraction is 50% or more, the composite film also tolerates treatment (heat setting) at temperatures of 80 to 100 °C.

[0075] However, more than 40% of >1.00g / cm 3 Even with high mass fractions of materials with densities of >0.95 g / cm, the film composite 3 As long as the film contains a sealant layer of a polyolefin-based material having a density of >1.00 g / cm, a failure or interruption of the process will always occur before a residual shrinkage of less than 5% in each of the MD and TD is achieved. This is because the temperature required for heat fixing the film must be at least 120-150°C, in which case the film will have a density of >1.00 g / cm. 3 This is because even materials with a melting temperature above 160° C., preferably above 170° C., having a density of 100° C., are no longer sufficient to keep the manufacturing process stable.

[0076] In order not to impair the manufacturing process of the film, only temperatures can be selected for the thermal post-treatment which do not completely eliminate shrinkage or contraction.

[0077] Nevertheless, to minimize or completely eliminate shrinkage, a further process step according to the invention is necessary. In addition to the treatment of the biaxially oriented film at temperature to eliminate shrinkage, a further process step, namely relaxation, is common, especially in the triple bubble or multi-bubble process. In this process, the film is allowed to shrink again in a controlled manner after stretching; this is known as relaxation and is carried out by the introduction of temperature or heat.

[0078] Relaxation may occur in both the production direction or machine direction (MD) and the cross direction to production (TD).

[0079] The relaxation may occur in the same way in both directions (MD and TD) or may occur in a different way in one or the other direction.

[0080] Furthermore, relaxation is possible only in one direction, i.e. only in MD or TD. The choice of relaxation direction can always be made independently. In the context of the present invention, the quantitative extent of relaxation is represented by the so-called relaxation coefficient, as defined in more detail below.

[0081] By "relaxation" is meant controlled or controlled shrink-back of the film in MD and / or TD. Controlled shrink-back in MD can be achieved by operating or hauling at different take-up speeds, i.e., the film take-up downstream of the relaxation process at a lower speed than the film take-up upstream of the process. In TD, controlled shrink-back is achieved by reducing the film width between the two film takes-ups. Examples of relaxation methods for extruded and oriented monolayer or multilayer films are known to the skilled person from Savic, Z., Savic. I, "Sausage Casings", VICTUS Lebensmittelindustriebedarf Vertriebsgesellschaft mbH, Vienna, 1st edition, 2002, chapter 7, subchapter 4.2, pages 267-270, especially figs 7-13a and 7-13b.

[0082] However, simply relaxing the film may not sufficiently reduce or even eliminate shrinkage.

[0083] This is due to the fact that films (shrink films / lidding films) are traditionally treated or fixed only at temperatures up to 60-80°C during relaxation, since this relatively low temperature is already sufficient to achieve a controlled shrink-back of the film and reduce the residual shrinkage to values ​​around 10-20% in MD and TD, respectively, but at most >5-10% in one of the two directions.

[0084] So far, lower shrinkage values ​​have not been achievable because neither the relaxation achievable at this condition (temperature) nor the temperature applied is sufficient to reduce the shrinkage below 5% in MD and TD, respectively.

[0085] The amount of shrinkage that can be achieved depends substantially on the level of temperature at which the film is treated or fixed.

[0086] Therefore, a maximum possible relaxation, which has an even more positive effect on the remaining residual shrinkage, ie which further reduces the residual shrinkage, can only be achieved at correspondingly high temperatures in the film processing (heat setting).

[0087] However, in this case the same problem occurs as above, namely that when a film, especially a film comprising a combination of raw materials with widely different melting temperatures, is treated at the temperatures required to eliminate shrinkage, softening or even melting of the individual layers occurs, thus inevitably interrupting or at least significantly impairing the film manufacturing process.

[0088] When treating a film with a combination of temperature and relaxation, the temperature range in which the manufacturing process is damaged or interrupted again depends on the mass fraction of the material in the layer structure of the film (density > 1.00 g / cm 3 ) depending on

[0089] However, it is surprising that the proper relaxation process results in a higher content of the material (density > 1.00 g / cm3) contained in the film than a dedicated heat treatment without relaxation. 3 ) can be significantly reduced.

[0090] Thus, with appropriate relaxation, significantly higher temperatures can be applied, in any case above 60°C, preferably above 70°C, in particular above 80°C, up to 180°C, preferably up to 150°C, in particular up to 120°C, while at the same time reducing the temperature of the material (>1.00 g / cm 3 It is possible to reduce the thermoplastic resin having a density of >1.00 g / cm 3 based on the total mass of the layer structure of the film to a mass fraction of in any case less than 40%, preferably less than 30%, in particular less than 20% and even less than 10%, based on the total mass of the layer structure of the film. In this case, 3 The mass fraction of thermoplastic resin having a density of at least 1%, preferably at least 5%.

[0091] Therefore, in the method according to the invention, the temperature of the composite film during relaxation can preferably be set in any one of the following ranges: 60 to 180°C, preferably 60 to 150°C, particularly preferably 60 to 120°C, most preferably 80 to 100°C.

[0092] In the method according to the invention, the residence time (dwell period) during relaxation, preferably during relaxation at temperature, is preferably 2 to 30 seconds, preferably 2 to 20 seconds, preferably 5 to 30 seconds, preferably 5 to 20 seconds, preferably 2 to 10 seconds or preferably 5 to 10 seconds.

[0093] In the method according to the invention, the residence time (dwell period) during relaxation, preferably during relaxation at temperature, is preferably 2 to 30 seconds, preferably 2 to 20 seconds, preferably 5 to 30 seconds, preferably 5 to 20 seconds, preferably 2 to 10 seconds or preferably 5 to 10 seconds.

[0094] As a result, in addition to the introduced fix temperature (temperature of the composite film during relaxation), the relaxation coefficient is a determining factor for again reducing or eliminating the shrinkage introduced during the stretching of the film.

[0095] In the context of the present invention, thus reducing or relaxing in a controlled manner the film stretch or elongation introduced during drawing has proven effective in achieving low shrinkage.

[0096] When considering the sum of the process steps, including stretching and then relaxing, there is a residual stretch or elongation in the film after both process steps. A residual stretch factor can be determined, which is defined in more detail below, and is based on the ratio of the length of a portion of the composite film after stretching and relaxing to the length of the same portion before stretching and relaxing.

[0097] The residual stretch coefficient is produced equally by both methods (stretching and relaxing) and therefore ideally can be influenced and varied equally by both methods.

[0098] A closer look at this dependence reveals that under otherwise identical conditions, reducing the stretch factor has a similar effect of slowing down the relaxation of the film, i.e., at low stretch, very low shrinkage is obtained even with little relaxation, whereas at high stretch, high relaxation is again required to keep shrinkage low. However, surprisingly, the effect of the relaxation factor is fundamentally much larger than that of the stretch factor.

[0099] However, the sum or factor of both process steps, not just the relaxation, is the determining factor.

[0100] Thus, the temperature at which relaxation is introduced, as well as the residual stretch coefficient, will essentially determine whether and to what extent the film will retain shrinkage.

[0101] The residual shrinkage rate is greatly affected not only by the relaxation process and the temperature introduced therein, but also by the stretching process, and since the stretching process is also subjected to temperature treatment, the influence of this process must also be taken into consideration.

[0102] Indeed, an effect can be seen here: lower stretching temperatures result in higher residual shrinkage compared to higher stretching temperatures, without a simultaneous change in the other parameters of the process.

[0103] However, compared to relaxation, the stretching process is much more sensitive, i.e. the temperatures required to obtain a stable process are often within a temperature window of only + / - 2 to + / - 3 ° C. Therefore, in this case the temperature range to be changed is smaller or limited.

[0104] Also, the effect of the temperature of the composite film during stretching is, according to the inventors' findings, rather small.

[0105] Thus, the temperature during the stretching of the composite film is an influencing factor, but does not have the same critical importance as temperature on the relaxation and stretch factor, as well as the relaxation factor or residual stretch factor.

[0106] A closer look at the process steps and their effects reveals another important factor: the time or duration of exposure of the film to each process step and the prevailing conditions.

[0107] However, it is found that the effect of the time factor on the stretching process is rather negligible compared to the effects of temperature and stretch factor.

[0108] On the other hand, in the method of relaxation, it has been found that the time (duration) of relaxation can be at least as important as the relaxation factors and the prevailing temperature.

[0109] The interaction of time (duration) and relaxation factors has been found to be less important than the time (duration) in relation to temperature, or more precisely, the duration of exposure of the film to temperature during relaxation.

[0110] The longer the duration of the temperature treatment, the greater its effect and therefore the greater the reduction in residual shrinkage.

[0111] However, this cannot be increased indefinitely, but rather it becomes evident that after a certain period under the influence of temperature, no further increase, i.e. reduction in shrinkage, can be realised and a sort of saturation is reached.

[0112] However, much more decisive is the period during which the film is at least / at least subject to the effect of temperature, where a period or residence time under temperature of at least 2 seconds is necessary to realize the desired effect.

[0113] The method according to the invention may therefore be limited in that the composite film has a temperature in one of the abovementioned temperature ranges for a certain period during relaxation (the so-called "dwell time at temperature"). The period of relaxation or the dwell time during relaxation at temperature should therefore preferably exceed at least 2 seconds, in particular 5 seconds. Thereby, the period of relaxation or the dwell time during relaxation at temperature may be limited to a maximum of 30 seconds, preferably a maximum of 20 seconds, in particular a maximum of 10 seconds.

[0114] Just as temperature or relaxation alone cannot bring about a correspondingly low shrinkage, neither can residence time at temperature alone. These influencing variables and the effects they achieve are interdependent and mutually influencing each other.

[0115] For example, high temperature treatment combined with high relaxation results in a film with low residual shrinkage (shrinkage after stretching and relaxation) despite a short residence time at temperature.

[0116] However, when processed at high temperatures and with long residence times at temperature, the film also exhibits low residual shrinkage, despite the lower relaxation.

[0117] Also, when the temperature residence time is long and the film has a high degree of relaxation despite moderate temperature treatment, the residual shrinkage of the film is low.

[0118] Therefore, only the combination of these influencing variables makes it possible to achieve the desired low residual shrinkage of the film.

[0119] Thus, to achieve low shrinkage in the claimed layer structure, not only the ideal layer structure, preferably by combination of the raw materials contained therein and the temperatures applied in the individual process steps, but also the process factors, in particular the stretch factor, relaxation factor and residual stretch factor, as well as the residence time, but at least the duration of heat setting (relaxation), are of decisive importance. By combining the features and parameters described herein or defined in the claims, the object of producing, in particular stably producing, a general composite film by lamination or coextrusion, preferably by coextrusion without lamination, is achieved for the first time, which, in addition to improved processability and / or recyclability, also includes other advantageous properties, such as heat resistance, printability, oxygen barrier, no shrinkage or a shrinkage rate of less than 5%, preferably less than 3%, in MD and TD, respectively.

[0120] It is particularly preferred that the thermoplastic resin contained in or made up of layer (c) has a melting point below 120° C. The increased temperature difference relative to the melting temperature of the outermost layer allows the composite film to be sealed earlier, i.e. already at a lower temperature, and higher cycle rates can be achieved during further processing of the composite film.

[0121] Furthermore, it is particularly preferred if the thermoplastic resin contained in or made up of layer (a) has a melting temperature of more than 160° C., preferably more than 170° C. The higher temperature of the outermost layer makes it possible to work at higher temperatures during further processing and therefore to achieve higher cycle rates during the further processing of the composite film.

[0122] Further, according to the present invention, the layer (a), i.e., the outermost layer, has a surface roughness of 10 dyn / cm (=10 -3 The polarity can advantageously be expressed in the form of a surface tension given in N / m. This value is preferably >40 dynes / cm (>40 10 -3 N / m), especially >42 dynes / cm (>42 10 -3 N / m) and allows for the best possible printability.

[0123] According to the invention, in an advantageous embodiment, it can further be provided that the outermost layer (a) consists of or comprises EVOH.

[0124] Up to now, no general composite film is known from the state of the art in which EVOH is used as a layer component of the outermost layer (a) or in which the layer (a) consists of EVOH. Thus, the use of EVOH as a material with good oxygen barrier properties is known from the state of the art. However, for this purpose, an inner position / arrangement is necessary since EVOH quickly loses its good oxygen barrier properties due to the penetration of moisture. Therefore, EVOH has only been used so far as a layer component or layer material sandwiched on both sides by protective layers such as polyolefins or polyamides, some of which also have high water vapor barrier properties. However, the use of EVOH in general composite films for different purposes, in different ways or in different arrangements, for example as an outermost layer or a sealant layer (innermost layer; surface facing the packaged article), has not been known so far.

[0125] In contrast, the present invention provides the possibility of purposefully using EVOH in layer (a), i.e., the outermost layer constituting the outer surface of the composite film. In this context, the outermost layer (a) may contain EVOH or may consist of EVOH. However, when EVOH is provided in the outermost layer (a), it is not the property of EVOH as an oxygen barrier that plays its role. Rather, what is important according to the present invention is that the use of EVOH in the outermost layer substantially increases the recyclability of the film compared to composite films containing PA or PET in the outermost layer. This is because EVOH contains a lower melting temperature compared to the PA and PET materials conventionally provided in the outermost layer, so that the difference in melting temperature between the outermost layer and the sealant layer (innermost layer) is smaller. This allows the overall melting temperature required for recycling to be reduced, improving the recyclability of the composite film.

[0126] The inventors have also found that the outermost layer of EVOH can further improve mechanical properties such as film stiffness and printability similar to PET and PA, compared to polyolefins such as PE or PP. For example, the melting temperature of EVOH is higher compared to these polyolefins, and the associated higher heat resistance of the innermost layer (sealant layer) leads to an overall improvement in further processability (number of cycles) of the composite film.

[0127] The method according to the present invention may further be configured as a method for producing a multi-layer composite film, the method comprising at least the following steps: Co-extruding and / or laminating at least four layers (a), (b), (d) and (c), Layer (a) forms the outer surface of the composite film; Layer (c) forms the surface of the composite film that faces or contacts the article to be packaged; and Layer (b) is disposed between layer (a) and layer (c); Layer (d) is disposed between layers (a) and (c), preferably between layers (a) and (b); wherein layer (b) consists of one or more layers (b1, b2, ...), preferably 2, 3 or 4 layers; wherein the layer (d) consists of one or more layers (d1, d2, ...), preferably 2, 3 or 4 layers; stretching the coextruded or laminated composite film; and relaxing the oriented or stretched composite film; wherein the stretching is biaxial; wherein the machine direction or longitudinal direction (MD) stretch factor is at least 2.0; the stretch factor in the transverse direction (TD) is at least 2.0; the sum of the machine direction (MD) stretch factor and the transverse direction (TD) stretch factor is at least 5.0; The composite film has a temperature of 70 to 130° C. during stretching; Machine direction (MD) relaxation factor > 0.00; Transverse direction (TD) relaxation factor > 0.00; the sum of the relaxation factors in the machine direction (MD) and the transverse direction (TD) is at least 0.05 (=5%), preferably at least 0.1 (=10%), preferably at least 0.2 (=20%), in particular at least 0.4 (=40%); The composite film has a temperature during relaxation of 60 to 180°C, preferably 60 to 150°C, more preferably 60 to 120°C, and particularly preferably 80 to 100°C; the residence time during relaxation, preferably during relaxation at temperature, is at least 2 seconds, more preferably more than 5 seconds, or the duration of relaxation is preferably at least 2 seconds, in particular more than 5 seconds; the residence time during relaxation, preferably during relaxation at temperature, is preferably at most 30 seconds, preferably at most 20 seconds, in particular at most 10 seconds, or the duration of relaxation is preferably at most 30 seconds, preferably at most 20 seconds, in particular at most 10 seconds; The residual stretch factor in the machine direction (MD) is up to 5; The residual stretch factor in the transverse direction (TD) is up to 5.0; Layer (a) has a density of at least 1.12 g / cm 3 comprising or consisting of an ethylene-vinyl alcohol copolymer (EVOH) having a density of The layer (d) or layers (d1, d2, ...) each have a density of 1.00 g / cm 3 Less than 0.98 g / cm 3 comprising or consisting of a thermoplastic resin, preferably a polyolefin, having a density less than The layer (b) or layers (b1, b2, ...) each have a density of 1.00 g / cm 3 and Layer (c) is 0.95 g / cm 3 The thermoplastic resin may comprise or consist of a thermoplastic resin having a density less than 1000 .mu.m.

[0128] Further advantageous embodiments of the method according to the invention are the subject matter of the dependent claims.

[0129] The above-mentioned method according to the invention and its advantageous embodiments may be further characterized as follows: Layer (b) does not contain EVOH; or None of the layers (b1, b2, ...) contains EVOH; or Layer (b) comprises or consists of EVOH; or At least one of the layers (b1, b2, ...) comprises or consists of EVOH; or None of the layers of the composite film other than layer (a) contains EVOH.

[0130] The method according to the invention and its advantageous embodiments described above may be further characterized as follows: The EVOH of layer (a) has a melting temperature of at least 160° C., preferably at least 170° C.; and / or the thermoplastic resin of layer (c) is a polyolefin having a sealing temperature lower than the sealing temperature of the thermoplastic resin of layer (a); and / or the thermoplastic resin of layer (c) is a polyolefin having a melting temperature below 120° C.; and / or The thermoplastic resin of layer (b) is 100 cm 3 / m 2 The thermoplastic resins of the layers (b1, b2, ...) have an oxygen permeability of less than 100 cm 3 / m 2 has an oxygen permeability of less than d bar; and / or Layer (b) is 100 cm 3 / m 2 The layers (b1, b2, ...) each or in total have an oxygen permeability of less than 100 cm 3 / m 2 contains an oxygen permeability of less than d bar; and / or The stretching is carried out simultaneously or successively in several stages; and / or the composite film after stretching and relaxation contains a shrinkage in the machine direction (MD) of less than 0.05 (=5%), preferably less than 0.03 (=3%); and / or the composite film after stretching and relaxation comprises a shrinkage in the transverse direction (TD) of less than 0.05 (=5%), preferably less than 0.03 (=3%); and / or Preferably, the composite film after stretching and relaxing has a sum of the shrinkage in the machine direction (MD) and the shrinkage in the transverse direction (TD) (=total shrinkage) of less than 0.05 (=5%).

[0131] The conjunction "and / or" expresses that the method according to the invention can be characterized by one, all or any selection or combination of the above-mentioned features. This definition applies analogously to the use of the conjunction "and / or" in the remainder of the specification and in the claims.

[0132] The above-mentioned method according to the invention and its advantageous embodiments may further be characterized as follows: the thickness of layer (a) does not exceed 20%, preferably 10%, of the total thickness of the composite film; and / or the thickness of layer (b) or the total thickness of layers (b1, b2, ...) does not exceed 20%, preferably 10%, of the total thickness of the composite film; and / or the mass fraction of layer (a) based on the total mass of the composite film does not exceed 10%; and / or the mass fraction of layer (b) or the sum of the mass fractions of layers (b1, b2, ...) based on the total mass of the composite film does not exceed 10%; and / or The sum of the mass fractions of layers (a) and (b) or layers (a) and layers (b1, b2, ...) does not exceed 10% based on the total mass of the composite film.

[0133] The above-described method according to the invention and its advantageous embodiments may further be characterized as follows: layer (a) does not contain at least one polymer of polyester, preferably polyethylene terephthalate (PET) or polylactic acid or polylactide (PLA), or polyamide (PA); and / or The thermoplastic resin of layer (c) comprises or consists of a polyolefin (PO), preferably polyethylene (PE) and / or polypropylene (PP), an ethylene-vinyl acetate copolymer (EVA), an ionomer (IO), an ethylene-methyl methacrylate copolymer (EMMA), an ethylene-methacrylic acid copolymer (EMA) or any mixture thereof.

[0134] The above-described method according to the invention and its advantageous embodiments provide a method for producing a composition having a viscosity of >1.0 g / cm 3 Layer components having a density of ≥ 1.12 g / cm 3 The mass fraction of EVOH in layer (a) having a density of is 1 to <40%, preferably 1 to <30%, preferably 1 to <20%, in particular 5 to <20%, based on the total mass of the composite film.

[0135] The object according to the invention is further solved by a multilayer, coextruded and / or laminated, biaxially oriented and relaxed composite film, produced according to the method according to the invention as described above and defined in the claims, whereby the composite film according to the invention comprises at least two layers (a) and (c), of which Layer (a) forms the outer surface of the composite film; and Layer (c) forms the surface of the composite film that faces or contacts the article to be packaged; and wherein layer (a) comprises or consists of an ethylene-vinyl alcohol copolymer (EVOH); and Layer (c) comprises or consists of a thermoplastic resin.

[0136] The advantages mentioned above in connection with the method according to the invention apply analogously to the composite film according to the invention and its variants.

[0137] According to the present invention the object is further solved by a multilayer, coextruded and / or laminated, biaxially oriented and relaxed composite film produced, or preferably produced, by the method according to the present invention, the composite film comprising at least three layers (a), (b) and (c), of which Layer (a) forms the outer surface of the composite film; Layer (c) forms the surface of the composite film that faces or contacts the article to be packaged; and layer (b) is disposed between layer (a) and layer (c); wherein layer (b) consists of one or more layers (b1, b2, b3, b4, ...), preferably two, three or four layers; The composite film has a residual stretch factor in the machine direction (MD) of at most 5.0; The composite film has a residual stretch factor in the transverse direction (MD) of at most 5.0; Layer (a) has a density of at least 1.12 g / cm 3 comprising or consisting of an ethylene-vinyl alcohol copolymer (EVOH) having a density of The layer (b) or layers (b1, b2, ...) each have a density of 1.00 g / cm 3 comprising or consisting of a thermoplastic resin having a higher density; and Layer (c) is 0.95 g / cm 3 The thermoplastic resin may comprise or consist of a thermoplastic resin having a density less than 1000 .mu.m.

[0138] According to the present invention the object is further solved by a multilayer, coextruded and / or laminated, biaxially oriented and relaxed composite film produced, or preferably produced, by the method according to the present invention, which comprises at least four layers (a), (b), (d) and (c), of which Layer (a) forms the outer surface of the composite film; Layer (c) forms the surface of the composite film that faces or contacts the article to be packaged; and layer (b) is disposed between layer (a) and layer (c); Layer (d) is disposed between layers (a) and (c), preferably between layers (a) and (b); wherein layer (b) consists of one or more layers (b1, b2, ...), preferably two, three or four layers; The layer (d) consists of one or more layers (d1, d2, ...), preferably two, three or four layers; The composite film has a residual stretch factor in the machine direction (MD) of up to 5.0; The residual stretch factor of the composite film in the transverse direction (TD) is up to 5.0; Layer (a) has a density of at least 1.12 g / cm 3 comprising or consisting of an ethylene-vinyl alcohol copolymer (EVOH) having a density of The layer (d) or layers (d1, d2, ...) each have a density of 1.00 g / cm 3 Less than 0.98 g / cm 3 comprising or consisting of a thermoplastic resin, preferably a polyolefin, having a density less than The layer (b) or layers (b1, b2, ...) each have a density of 1.00 g / cm 3 comprising or consisting of a thermoplastic resin having a higher density; and Layer (c) is 0.95 g / cm 3 The thermoplastic resin may comprise or consist of a thermoplastic resin having a density less than 1000 .mu.m.

[0139] Advantageous embodiments of the composite film according to the invention are the subject of the dependent claims.

[0140] Thus, the composite film according to the invention may be characterized as follows: The thermoplastic resin of layer (b) is 100 cm 3 / m 2 The thermoplastic resins of the layers (b1, b2, ...) have an oxygen permeability of less than 100 cm 3 / m 2 has an oxygen permeability of less than d bar; and / or Layer (b) is 100 cm 3 / m2 The layers (b1, b2, ...) each or in total have an oxygen permeability of less than 100 cm 3 / m 2 has an oxygen permeability of less than d bar; and / or the thickness of layer (b) or the total thickness of layers (b1, b2, ...) does not exceed 20%, preferably 10%, of the total thickness of the composite film; and / or the mass fraction of layer (b) or the sum of the mass fractions of layers (b1, b2, ...) based on the total mass of the composite film does not exceed 10%; and / or The sum of the mass fractions of layers (a) and (b), or layers (a) and (b1, b2, ...), based on the total mass of the composite film, does not exceed 10%.

[0141] Furthermore, the composite film according to the present invention can be characterized as follows: The EVOH of layer (a) has a melting temperature of at least 160° C., preferably at least 170° C.; and / or the thermoplastic resin of layer (c) is a polyolefin having a sealing temperature lower than the sealing temperature of the EVOH of layer (a); and / or The thermoplastic resin of layer (c) is a polyolefin having a melting temperature below 120°C.

[0142] Furthermore, the composite film according to the present invention can be characterized as follows: the composite film, after stretching and relaxing, has a sum of the shrinkage in the machine direction (MD) and the shrinkage in the transverse direction (TD) (=total shrinkage) of less than 0.05 (=5%); and / or the thickness of layer (a) does not exceed 20%, preferably 10%, of the total thickness of the composite film; and / or Layer (a) does not comprise at least one of the following types of polymers: polyester, preferably polyethylene terephthalate (PET), or polylactic acid or polylactide (PLA), or polyamide (PA); and / or the thermoplastic resin of layer (c) comprises or consists of a polyolefin (PO), preferably polyethylene (PE) and / or polypropylene (PP), an ethylene-vinyl acetate copolymer (EVA), an ionomer (IO), an ethylene-methyl methacrylate copolymer (EMMA), an ethylene-methacrylic acid copolymer (EMA) or any mixture thereof; and / or >1.0g / cm 3 Layer components having a density of ≥ 1.12 g / cm 3 The mass fraction of EVOH in layer (a) having a density of from 1 to <40%, preferably from 1 to <30%, preferably from 1 to <20%, in particular from 5 to <20%, based on the total mass of the composite film.

[0143] According to the invention, the object is furthermore achieved by the use of a composite film according to the invention as defined in the claims or as described above, or a casing produced therefrom, for packaging an article, preferably a food, a luxury item or a liquid or solid, in particular a powdery article.

[0144] In an advantageous embodiment, the use according to the invention provides a composition having a viscosity of >1.0 g / cm 3 of layer components having a density of preferably ≥ 1.12 g / cm 3 The mass fraction of EVOH in layer (a) having a density of from 1 to <40%, preferably from 1 to <30%, preferably from 1 to <20%, in particular from 5 to <20%, based on the total mass of the composite film.

[0145] The advantages discussed above in connection with the method according to the invention apply analogously to the use of the composite film according to the invention and its modification.

[0146] Supplemental Disclosures The methods of making the inventive multilayer composite films described herein may be characterized as not including a step of laminating, i.e. adhering, layers or layer composites.

[0147] Thus, the multi-layer composite film described herein according to the present invention may be a non-laminated composite film.

[0148] Length definitions (based on machine direction or cross direction respectively): L0:=length of a given section of the composite film before stretching; L1:=the length of an identical section of the composite film after stretching and before relaxation; L2:=the length of the same section of the composite film after stretching and before relaxation; L3:=the length of the same section of the composite film after stretching and relaxation;

[0149] Definition of stretch factor: stretch factor V = length L1 of a given section of a composite film after stretching and before relaxation divided by length L0 of the same section of the composite film before stretching; (V = L1 / L0)

[0150] Definition of relaxation factor: Relaxation factor RL = the difference between the length L3 of a given section of a composite film after stretching and relaxation and the length L2 of the same section of the composite film after stretching and before relaxation, divided by the length L2 of the same section of the composite film after stretching and before relaxation; (RL = |(L3-L2)| / L2)

[0151] Definition of residual stretch factor: Residual stretch factor RV = length L3 of a given section of a composite film after stretching and relaxation divided by length L0 of the same section of the composite film before stretching and relaxation; (RV = L3 / L0)).

[0152] Preferably, the composite film according to the present invention is a multi-layer composite film or a multi-layer barrier film having a barrier function, where barrier property refers to reduced oxygen permeability or reduced water vapor permeability, or both.

[0153] Shrinkage (or heat shrinkage): Measured in 90°C water preferably within 1 second after immersion, but at least within 10 seconds after immersion.

[0154] According to the invention, to measure the shrinkage (or heat shrinkage), the sample is immersed in water at 90° C. for a given time, in particular for the times mentioned above, and immediately cooled to room temperature with water after removal. The length of the pre-marked section after this treatment is measured and referenced to the length measurement of the same section of the sample before treatment. The resulting length ratio ("shrink" vs. "unshrink") is expressed as a percentage and defines the shrinkage. Depending on the direction of the length measurement, the shrinkage in the machine direction (MD) and the transverse direction (TD) is obtained. The total shrinkage is calculated by adding the shrinkage in the machine direction and the transverse direction. Multiple measurements of the length measurement, for example triplicate or quintuplicate measurements, and the formation of corresponding average values ​​therefrom, advantageously increase the accuracy of the measurement. According to the invention, the shrinkage and the total shrinkage can be determined in particular according to ASTM 2732.

[0155] In the present invention, oxygen permeability is measured at 23° C. and a relative humidity of 75% (ASTM D1434).

[0156] The method according to the invention and the composite film according to the invention can preferably be carried out or produced using the so-called double bubble process, in particular the triple bubble process, for which the applicant provides suitable equipment known to the skilled person. In this process, the multilayer composite film can be coextruded from the respective resin melts, preferably with thermal separation of the individual layers, for example by the applicant's nozzle blow head, which is installed to produce a composite film having three or more layers, cooled by the applicant's water cooling system, reheated, biaxially oriented (machine direction (MD) and transverse direction (TD)) by a sealed compressed air bubble, and finally relaxed (= heat set or heat fixed) in a further step in a defined temperature range. The composite film according to the invention can be a composite film which comprises a barrier against gas diffusion, in particular against oxygen diffusion, and / or against water vapor diffusion. Such manufacturing methods are also known to those skilled in the art from the textbook "Sausage Casings" by Savic, Z. and Savic, I., 1st edition, 2002, VICTUS Lebensmittelindustriebedarf Vertriebsgesellshaft mbH, Vienna, Austria, Chapter 7, in particular Chapter 4.2, pages 267-270.

[0157] Another method of producing films according to the invention is by stretching a coextruded flat film according to tenter frame techniques known to those skilled in the art.

[0158] The composite film according to the invention can be advantageously obtained in an apparatus or plant of the same applicant for the production of tubular food films for food packaging, such as shrink films or shrink bags, by the jet-blowing process, by additionally using a device for rapid cooling of the thin thermoplastic tube after its extrusion, as disclosed in the same applicant's patent specification DE 199 16 428 B4. For this purpose, the corresponding further development according to patent specification DE 100 48 178 B4 can also be considered.

[0159] In this method, the tubular film produced from the plastic melt in the nozzle blow head is intensively cooled, during which the amorphous structure of the thermoplastic from the plastic melt is preserved. The tubular film extruded vertically from the plastic melt in the nozzle blow head initially travels without contact with the walls in the cooling device for cooling, as described in detail in DE 199 16 428 B4 and DE 100 48 178 B4. In order to avoid repetition, reference is made in its entirety to the contents of DE 199 16 428 B4 and DE 100 48 178 B4 for details of the method, structure and operation of this cooling system, also called the calibration device.

[0160] The tubular film then passes through a support in a cooling system against which it is supported as a result of a pressure difference between the interior of the tubular film and the coolant, maintaining a liquid film between the film and the support and preventing sticking of the tubular film, whereby the diameter of the support influences the diameter of the tubular film, and for this reason this cooling system of the applicant is also called a calibrated system.

[0161] According to the invention, the polyamide (PA) may be a PA of ε-caprolactam or poly(ε-caprolactam) (PA6), a PA of hexamethylenediamine and adipic acid or polyhexamethyleneadipamide (PA6.6), a PA of ε-caprolactam and hexamethylenediamine / adipic acid (PA6.66), a PA of hexamethylenediamine and dodecanedioic acid or polyhexamethylenedodecanamide (PA6.12), a PA of 11-aminoundecanoic acid or polyundecaneamide (PA11), a PA of 12-laurinlactam or poly(ω-laurinlactam) (PA12), or a mixture of these PAs, or a mixture of these PAs with amorphous PAs or other polymers. The general notation PAx.y is synonymous with PAx / y or PAxy.

[0162] For the purposes of this application, polyolefin (PO) may be a material selected from the group consisting of PP, PE, LDPE, LLDPE, polyolefin plastomer (POP), ethylene-vinyl acetate copolymer (EVA), ethylene-methyl methacrylate copolymer (EMMA), ethylene-methacrylic acid copolymer (EMA), ethylene-acrylic acid copolymer (EAA), cycloolefin / cycloalkene and 1-alkene copolymers or cycloolefin copolymers (COC), ionomers (IO) or mixtures or blends thereof. Furthermore, in the context of the present invention, PO also includes blends of said PO with ionomers and / or with adhesion promoters.

[0163] In the context of the present invention, polyesters may be used as layer components of layer (a). Polyesters are polymers with ester functional groups in the main chain, and may in particular be aliphatic or aromatic polyesters. Polyesters can be obtained by polycondensation of the corresponding dicarboxylic acids with diols. Any dicarboxylic acid suitable for forming polyesters can be used to synthesize polyesters, including in particular terephthalic acid and isophthalic acid, as well as dimers of unsaturated aliphatic acids. As further components for the synthesis of polyesters, diols can be used, including, for example: polyalkylene glycols, such as ethylene glycol, propylene glycol, tetramethylene glycol, neopentyl glycol, hexamethylene glycol, diethylene glycol, polyethylene glycol and polytetramethylene oxide glycol; 1,4-cyclohexane dimethanol and 2-alkyl-1,3-propanediol.

[0164] In particular, PET, an abbreviation of polyethylene terephthalate, is preferred. PET can be obtained by polycondensation of terephthalic acid (1,4-benzenedicarboxylic acid) and ethylene glycol (1,2-dihydroxyethane).

[0165] Another preferred polyester is polylactide or polylactic acid (PLA), which may be included as a layer component in the layer providing the polyester as a layer component. These polymers are biocompatible / biodegradable and include high melting temperatures or points and good tensile strength in addition to low moisture absorption.

[0166] In the context of the present invention, EVOH means not only EVOH, but also blends of EVOH with other polymers, ionomers, EMA or EMMA. In particular, EVOH also includes blends of EVOH and PA or blends of EVOH and ionomers.

[0167] The adhesion promoter (HV) may be provided as an intermediate layer in the composite film according to the invention and represents an adhesive layer that provides good bond adhesion between the individual layers. In this context, the HV may be based on a substrate selected from the group consisting of PE, PP, EVA, EMA, EMMA, EAA and ionomers, or mixtures thereof. Particularly suitable adhesion promoters (HV) according to the invention are EVA, EMA or EMMA, each with a purity of >99%, preferably >99.9%.

[0168] According to further preferred embodiments, the layer comprising a HV as a layer component may comprise a mixture of PO and HV, or a mixture of EVA, EMA, EMMA and / or EAA with HV, or a mixture of ionomer and HV, or a mixture of several HVs.

[0169] For the purposes of the present invention, the melting point of the polymer is determined by means of dynamic differential calorimetry or differential thermal analysis according to DIN 51007:2019-04 or DIN EN ISO 11357-1:2017-02. Alternatively, the ASTM D3418 method is also known from the state of the art.

[0170] For the purposes of the present invention, the softening point of a polymer is determined in accordance with the method for determining the Vicat softening temperature (VST) according to DIN EN ISO 306:2014-03.

[0171] For the purposes of the present invention, printability is measured in accordance with DIN 16500-2:2018-09.

[0172] For the purposes of the present invention, the description of a material as a "layer component" means that a layer of a composite film according to the invention at least partially comprises this material. In this context, the description "layer component" in the sense of the present invention may in particular include that the layer consists entirely or exclusively of this material.

[0173] For the purposes of the present invention, an "intermediate" or "intermediate" layer means a layer of a composite film that is disposed between layers (a) and (c). According to the present invention, layer (a) is the layer that forms the outer surface of the composite film (the outermost layer). According to the present invention, layer (c) is the layer that forms the surface of the composite film that faces or contacts the article to be packaged (the innermost layer). By definition, layers (a) and (c) of a composite film according to the present invention cannot be "intermediate" or "intermediate" layers.

[0174] Preferably, the composite film according to the present invention is in the form of a sheet or a tube. Preferably, the composite film is a food film or a food casing. More preferably, the composite film is suitable for use as a non-heat shrinkable packaging material.

[0175] Example of a coextruded and biaxially oriented multilayer film with barrier function according to the present invention having at least three layers (a), (b) and (c)

[0176] [Table 13]

[0177] Example of a coextruded and biaxially oriented multilayer film with barrier function according to the present invention having at least four layers (a), (b), (d) and (c)

[0178]

Table 14

[0179]

Table 15

[0180]

Table 16

[0181]

Table 17

Claims

1. A method for producing a multi-layer composite film, comprising at least the following steps: co-extruding and / or laminating at least three layers (a), (b) and (c); Layer (a) forms the outer surface of the composite film; Layer (c) forms the surface of the composite film that faces or contacts the article to be packaged; and layer (b) is disposed between layer (a) and layer (c); wherein layer (b) consists of a single layer or multiple layers (b1, b2, b3, b4, ...); stretching the coextruded or laminated composite film; and Relaxing the oriented composite film. Including; wherein the stretching is biaxial; a machine direction or longitudinal direction (MD) stretch factor of at least 2.0; the transverse direction (TD) stretch factor is at least 2.0; the sum of the machine direction (MD) stretch factor and the transverse direction (TD) stretch factor is at least 5.0; The composite film has a temperature of 70-130° C. during stretching; a machine direction (MD) relaxation factor greater than 0.00; The relaxation coefficient in the transverse direction (TD) is greater than 0.00; the sum of the machine direction (MD) relaxation modulus and the transverse direction (TD) relaxation modulus is at least 0.05; The composite film has a temperature during relaxation of 60 to 180°C; During the relaxation, the residence time during the relaxation at temperature is at least 2 seconds and at most 30 seconds; a residual stretch factor in the machine direction (MD) of at most 5.0; The residual stretch factor in the transverse direction (TD) is at most 5.0; Layer (a) has a density of at least 1.12 g / cm 3 comprising or consisting of an ethylene-vinyl alcohol copolymer (EVOH) having a density of The layer (b) or layers (b1, b2, ...) each have a density of 1.00 g / cm 3 comprising or consisting of a thermoplastic resin having a density greater than Layer (c) is 0.95 g / cm 3 23. A method of manufacturing comprising or consisting of a thermoplastic resin having a density less than 2000 MPa.

2. 2. The method of claim 1, comprising the steps of: co-extruding and / or laminating at least four layers (a), (b), (d) and (c); layer (d) is disposed between layer (a) and layer (c); wherein the layer (d) consists of a single layer or multiple layers (d1, d2, ...); The layer (d) or layers (d1, d2, ...) each have a density of 1.00 g / cm 3 Containing or consisting of a thermoplastic resin having a density less than The manufacturing method according to claim 1,

3. Layer (b) does not contain EVOH; or None of the layers (b1, b2, ...) comprises EVOH; or Layer (b) comprises or consists of EVOH; or At least one of the layers (b1, b2, ...) comprises or consists of EVOH; or None of the layers of the composite film other than layer (a) contains EVOH. The method according to claim 1 or 2, characterized in that

4. The EVOH of layer (a) has a melting temperature of at least 160° C.; and / or the thermoplastic resin of layer (c) is a polyolefin having a sealing temperature lower than the sealing temperature of the thermoplastic resin of layer (a); and / or The thermoplastic resin of layer (c) is a polyolefin having a melting temperature below 120° C.; and / or The thermoplastic resin of layer (b) is 100 cm 3 / m 2 have an oxygen permeability of less than d bar, or the thermoplastic resins of the layers (b1, b2, ...) each or together have a thickness of less than 100 cm 3 / m 2 has an oxygen permeability of less than d bar; and / or Layer (b) is 100 cm 3 / m 2 - has an oxygen permeability of less than d bar, or the layers (b1, b2, ...) each or together have a thickness of less than 100 cm 3 / m 2 - has an oxygen permeability of less than d bar; and / or The stretching is carried out simultaneously or successively in several stages; and / or the composite film after stretching and relaxing has a shrinkage in the machine direction (MD) of less than 0.05; and / or the composite film after stretching and relaxing comprises a shrinkage in the transverse direction (TD) of less than 0.05; and / or The composite film after stretching and relaxing contains a sum of machine direction (MD) shrinkage and transverse direction (TD) shrinkage (=total shrinkage) of less than 0.

05. The method according to any one of claims 1 to 3, characterized in that

5. the thickness of layer (a) does not exceed 20% of the total thickness of the composite film; and / or the thickness of layer (b) or the total thickness of layers (b1, b2, ...) does not exceed 20% of the total thickness of the composite film; and / or the mass fraction of layer (a) relative to the total mass of the composite film does not exceed 10%; and / or the mass fraction of layer (b) or the sum of the mass fractions of layers (b1, b2, ...) does not exceed 10%, based on the total mass of the composite film; and / or The sum of the mass fractions of layers (a) and (b) or the sum of the mass fractions of layers (a) and (b1, b2, ...) does not exceed 10% based on the total mass of the composite film. The method according to any one of claims 1 to 4, characterized in that

6. and / or layer (a) does not comprise at least one of the following types of polymers: polyethylene terephthalate (PET) or polylactic acid or polylactide (PLA) or polyamide (PA); and / or The thermoplastic resin of layer (c) comprises or consists of polyolefin (PO), ethylene-vinyl acetate copolymer (EVA), ionomer (IO), ethylene-methyl methacrylate copolymer (EMMA), ethylene-methacrylic acid copolymer (EMA) or any mixture thereof. The method according to any one of claims 1 to 5, characterized in that

7. >1.0 g / cm 3 7. The method according to claim 1 , wherein the mass fraction of the layer components having a density of from 1 to <40%, based on the total mass of the composite film.

8. at least three layers (a), (b) and (c); Layer (a) forms the outer surface of the composite film; Layer (c) forms the surface of the composite film that faces or contacts the article to be packaged; and layer (b) is disposed between layer (a) and layer (c); wherein layer (b) consists of a single layer or multiple layers (b1, b2, b3, b4, ...); the residual stretch factor of the composite film in the machine direction (MD) is at most 5.0; The residual stretch factor of the composite film in the transverse direction (TD) is at most 5.0; wherein the layer (a) has a density of at least 1.12 g / cm 3 comprising or consisting of an ethylene-vinyl alcohol copolymer (EVOH) having a density of The layer (b) or layers (b1, b2, ...) each have a density of 1.00 g / cm 3 comprising or consisting of a thermoplastic resin having a higher density; and Layer (c) is 0.95 g / cm 3 comprising or consisting of a thermoplastic resin having a density of less than Multilayer, coextruded, and / or laminated, biaxially oriented and relaxed composite films.

9. at least four layers: (a), (b), (d) and (c); - layer (d) is disposed between layer (a) and layer (c); wherein the layer (d) consists of a single layer or multiple layers (d1, d2, ...); The layer (d) or layers (d1, d2, ...) each have a density of 1.00 g / cm 3 comprising or consisting of a thermoplastic resin having a density of less than 9. The multilayer, coextruded, and / or laminated, biaxially oriented and relaxed composite film of claim 8.

10. Layer (b) does not contain EVOH; or None of the layers (b1, b2, ...) comprises EVOH; or Layer (b) comprises or consists of EVOH; or At least one of the layers (b1, b2, ...) comprises or consists of EVOH; or None of the layers of the composite film other than layer (a) contains EVOH.

10. The composite film according to claim 8 or 9,

11. The thermoplastic resin of layer (b) is 100 cm 3 / m 2 have an oxygen permeability of less than d bar, or the thermoplastic resins of the layers (b1, b2, ...) each or together have a thickness of less than 100 cm 3 / m 2 has an oxygen permeability of less than d bar; and / or Layer (b) is 100 cm 3 / m 2 - have an oxygen permeability of less than d bar, or the layers (b1, b2, ...) each or together have a thickness of less than 100 cm 3 / m 2 has an oxygen permeability of less than d bar; and / or the thickness of layer (b) or the total thickness of layers (b1, b2, ...) does not exceed 20% of the total thickness of the composite film; and / or the mass fraction of layer (b) or the sum of the mass fractions of layers (b1, b2, ...) based on the total mass of the composite film does not exceed 10%; and / or The mass fraction of layers (a) and (b) or the sum of the mass fractions of layers (a) and (b1, b2, ...) based on the total mass of the composite film does not exceed 10%. The composite film according to any one of claims 8 to 10,

12. The EVOH of layer (a) has a melting temperature of at least 160° C.; and / or the thermoplastic resin of layer (c) is a polyolefin having a sealing temperature lower than the sealing temperature of the EVOH of layer (a); and / or The thermoplastic resin of layer (c) is a polyolefin having a melting temperature lower than 120° C. The composite film according to any one of claims 8 to 11,

13. 13. A composite film according to any one of claims 8 to 12, characterized in that after stretching and relaxing the composite film has a sum of the machine direction (MD) shrinkage and the transverse direction shrinkage (=total shrinkage) of less than 0.

05.

14. A composite film according to any one of claims 8 to 13, characterized in that the thickness of layer (a) does not exceed 20% of the total thickness of the composite film.

15. Layer (a) does not comprise at least one of the following types of polymers: polyethylene terephthalate (PET) or polylactic acid or polylactide (PLA), or polyamide (PA); and / or The thermoplastic resin of layer (c) comprises or consists of polyolefin (PO), ethylene-vinyl acetate copolymer (EVA), ionomer (IO), ethylene-methyl methacrylate copolymer (EMMA), ethylene-methacrylic acid copolymer (EMA) or any mixture thereof. The composite film according to any one of claims 8 to 14,

16. >1.0 g / cm 3 16. The composite film according to claim 8, wherein the mass fraction of the layer components having a density of from 1 to <40%, based on the total mass of the composite film.

17. Use of a multilayer composite film according to any one of claims 8 to 16 or a casing made from said multilayer composite film for packaging an article.

18. >1.0 g / cm 3 18. Use according to claim 17, characterized in that the mass fraction of the layer components having a density of from 1 to <40%, based on the total mass of the composite film.

19. At least 1.12 g / cm in a layer of the multilayer composite film 3 said layer forming an outer surface of a multi-layer composite film; and The multilayer composite film is coextruded and / or laminated, biaxially oriented and relaxed.

Citation Information

Patent Citations

  • Multilayer oriented film its manufacture

    JP1992115926A

  • Multilayer oriented film and its manufacture

    JP1992115927A

  • Multilayer stretched film and preparation thereof

    JP1992164640A

  • Multilayer stretched film and preparation thereof

    JP1992164641A

  • Multi-layer film

    JP1992185322A